Trading and military cooperation between colombia and the united states, 1946-1953 (2013)
This paper show the main economic and military cooperation treaties between Colombia and United States governments, during the first years after World War II, when the Cold War began and the United States adopted a policy of economic liberalism. Within this framework a new commerce and friendship agreement took place between them, and the Colombian government opened his doors to foreign capitals. Furthermore, the military treaties between both countries strengthen in those years, due to the United States idea of a hemispheric defense against the international communism, and the Colombian intention to improved their armed forces formation and modernization.